Career development and public policy - Watts, Anthony G. (Orientación y Sociedad.)
The rationale for policy interest in career development services, and the way in which this rationale is being strengthened by the current transformations in work and career, are discussed. The potential roles of public policy in relation to career development services are explored, along with ways in which such services can influence the policy-making process. A range of policy issues related to making career development services available to all throughout life are identified: these include the nature of such services, where they are to be located, and who is to pay for them. It is argued that there is a need for stronger structures and processes to bring together career development practitioners with policy- makers and other stakeholder interests in order to address tasks of common concern, at both national and international levels.